2011
DOI: 10.1111/j.1532-950x.2011.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tibial Tuberosity Advancement on the Contact Mechanics and the Alignment of the Patellofemoral and Femorotibial Joints

Abstract: TTA restored the normal FT and PF alignment, and reduced the retropatellar force by about 20%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 49 publications
4
48
0
1
Order By: Relevance
“…Tibial tuberosity advancement (TTA) is designed to align the patellar tendon perpendicularly relative to the tibial plateau, by displacing the tibial tuberosity cranially. This advancement neutralizes tibiofemoral shear forces and allows return to function despite deterioration of the cranial cruciate ligament (CrCL) in the dog stifle . TTA is an accepted surgical procedure to manage lameness associated with cruciate ligament disease in dogs .…”
Section: Introductionmentioning
confidence: 99%
“…Tibial tuberosity advancement (TTA) is designed to align the patellar tendon perpendicularly relative to the tibial plateau, by displacing the tibial tuberosity cranially. This advancement neutralizes tibiofemoral shear forces and allows return to function despite deterioration of the cranial cruciate ligament (CrCL) in the dog stifle . TTA is an accepted surgical procedure to manage lameness associated with cruciate ligament disease in dogs .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the quadriceps muscle group was transected. Other studies evaluating cranial cruciate ligament disease have utilized a spring to simulate the function of the quadriceps mechanism [22, 23]. This was not performed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Because the most profound femorotibial kinematic abnormalities with cranial cruciate ligament rupture occur in the sagittal plane, it is logical to expect that the patellofemoral kinematics we reported, including patellar flexion, proximodistal translation, and craniocaudal translation, may be disrupted by the condition. Indeed, cadaveric studies have found the cranial cruciate ligament rupture can alter patella alignment and patellofemoral contact mechanics [4]. Patellofemoral mechanics are also of particular interest with the surgical treatment of cranial cruciate ligament rupture as stifle extensor mechanism abnormalities frequently occur following various procedures used to address the disease [26].…”
Section: Discussionmentioning
confidence: 99%
“…Patellar luxation is a highly prevalent disorder affecting the stifles of dogs and alters stifle mechanics [2]. Cranial cruciate ligament insufficiency is also common in dogs and has been shown to disrupt normal patellofemoral joint motion [3, 4]. …”
Section: Introductionmentioning
confidence: 99%